Resensi Buku:: Mengajar untuk Mengubah Hidup - Ong Lie Hien (TRANSFORMATIO: Jurnal Teologi, Pendidikan, dan Misi Integral, 2023)
Howard G. Hendrick is an educator and Christian leader who has dedicated his life to Christian education for more than 50 years. Talbot School of Theology, Biola University in California, America even designated him as one of the Christian educators of the twentieth century who had an influence in shaping Christian education. This can also be seen from the Christian leaders he has trained and who have become people who have had an influence in the world of Christianity.